Prevalence of leptospira in abattoir workers, slaughtered animals and abattoir environment in Cavite, Philippines - Tabo, Norbel A.
Leptospirosis is known to b endemic in the Philippines with disease incidence that peaks during rainy season or after heavy rains in flood-prone areas. During summer, occupationally at-risk groups such as farmers, abbatoir workers, and garbage collectors are affected. Strategies to prevent and control leptospirosis have been done for years yet the number of cases continues to be high. The aim of this study was to determine the prevalence of antibodies to Leptospira among abattoir workers and slaughtered animals, and Leptospira serovars in slaughtered animals and abattoir environment in Cavite, Philippines. Serum samples obtained from 46 abattoir workers and 69 slaughtered animals were subjected to microscopic agglutination test (MAT). The MAT-screening positive sera were further subjected to MAT quantitation with a cut-off titer of 400 in humans and 20 animals. The urine of 69 slaughtered animals and 72 environmental samples were subjected to culture. Culture-positive samples were subjected to rrl-PCR, flaB-PCR and serotyping using monoclonal/polyclonal antibodies. The results showed that 15.2% of abattoir workers in selected abattoirs of Cavite province were positive for Leptospira-agglutinating antibodies, that reacted with serovars Canicola, Hurtsbridge, Losbanos, Poi and Ratnapura. These workers were assigned in dehairing, abattoir cleaning and butchering of pigs, and gut removal, gut cleaning, hide removal, and butchering in cows. On the other hand, the overall Leptospira-seropositivity in slaughtered animals was 58.0%, 61.7% of which was in pigs and 33.3% in cows. The most frequently occurring serovars in pigs was Poi with 38.3%, followed by Icterohaemmorrhagiae strain Ictero No. 1 (18.3%), Copenhageni (16.7%), Semaranga (10.0%) and Icterohaemorragiae strain RGA (8.3%). However, the most frequently occurring serovars in cows was Poi (22.2%). Twenty five percent (18/72) of the environmental samples were positive for Leptospira. Of these, 5 samples were positive for flaB-PCR. These samples were considered as pathogenic and were observed in Noveleta, Imus City and Bacoor abattoir. Of the five pathogenic isolates, one isolate reacted with serogroup Grippotyphosa while the remaining four isolates did not react with any of the monoclonal and polyclonal antibodies. On the other hand, none of the 69 urine samples were positive for culture. The presence of common serovars at the interface of both abattoir workers-slaughtered animals, and slaughtered animals-abattoir environment could indicate continual source of leptospires and could pose problems on human health. These serovars could be potential candidates for the development of vaccince and diagnostic tests.